Unfolding and refolding occur much faster for a proline-free proteins than for most proline-containing proteins. - Brandts, J F (1977)
The kinetics for unfolding and refolding of a parvalbumin (band 5) have been examined as a function of pH near the transition region, using stopped-flow techniques. This protein is rather unusual in that it has no proline residues, and therefore serves as a good example to test the hypothesis that the rate-limiting step seen in denaturation reactions is due to the cis-trans isomerization of proline peptide bonds in the denatured state. The kinetics for parvalbumin unfolding and refolding are complex, with the data being resolvable into two fast phases at 25 degrees. The slower of the two phases seen for the parvalbumin is about 100 to 500 times faster than the slow phase seen for proline-containing proteins under the same conditions! These results argue strongly in support of the proline isomerization hypothesis. It is also suggested that the slower phase seen for parvalbumin and the second-slowest phase seen for proline-containing proteins might be due to the cis-trans isomerization of peptide bonds of non-proline residues.